Interaksi Pimpinan dalam Peningkatan Perceived Quality pada Karyawan Waterboom Jaya Tirta Abadi - Yuditha, Alma; Pamungkas, Indra Novianto Adibayu; Pramesthi, Jasmine Alya (Jurnal Pustaka Komunikasi, 2025)
In an increasingly competitive business environment, it is important for entrepreneurs to maintain their position and plan effective business strategies. One important factor is consumer trust, which is influenced by positive perceive quality. To achieve this goal, effective organizational communication and leadership are needed to drive the organization and set clear goals. This study focuses on the leadership interaction in enhancing the positive perception of company quality among employees of Waterboom Jaya Tirta Abadi Purwakarta, a tourism business. The research used a qualitative approach with a case study methode, collecting data through interviews and literature reviews, and using source and technique triangulation for data validity. The results indicate that organizational communication and the interaction between leaders and employees has successfully enhanced the positive perception of company quality, particularly through clear information and guidance as well as positive interactions between employees and visitors. However, issues arise from the lack of formal organizational structure and operational standards, as well as inadequate resources. Nevertheless, the contributions of leaders and employees are expected to enhance the positive perception of company quality by consumers.